2007
DOI: 10.1590/s1676-24442007000500003
|View full text |Cite
|
Sign up to set email alerts
|

Soroprevalência da hepatite B e avaliação da resposta imunológica à vacinação contra a hepatite B por via intramuscular e intradérmica em profissionais de um laboratório de saúde pública

Abstract: J Bras Patol Med Lab • v. 43 • n. 5 • p. 313-318 • outubro 2007

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
2
13

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 23 publications
0
2
2
13
Order By: Relevance
“…The anti-HBs dosage in this study was lower than previously reported among PHC workers (14)(15) . As for the factors associated with the anti-HBs dosage, it was found an association between the amount of time they were working for the FHS and higher levels of anti-HBs (p=0.05), which may be related to the fact that possibly these workers had more opportunities to be vaccinated, perhaps through campaigns or updates, or by perception of need, only after exposure to biological or sharp instruments.…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…The anti-HBs dosage in this study was lower than previously reported among PHC workers (14)(15) . As for the factors associated with the anti-HBs dosage, it was found an association between the amount of time they were working for the FHS and higher levels of anti-HBs (p=0.05), which may be related to the fact that possibly these workers had more opportunities to be vaccinated, perhaps through campaigns or updates, or by perception of need, only after exposure to biological or sharp instruments.…”
Section: Discussioncontrasting
confidence: 85%
“…Thus, it was found that the number of reports of immunity verification in this study was lower than those reported in prior studies (5,15) and higher than in Divinópolis (11) , since the number of immunity reports was lower in this study. The anti HBs dosages reported in this study were much lower than those reported in previous studies (14)(15) , this worrisome factor suggests the need for up to date informational courses to these workers, evaluating the effectiveness of the city vaccination rooms. It should be noted, however, that the low prevalence of registered immunity may be due to the time elapsed after the last dose of HB vaccine (3) .…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Luz et al (2004) observaram em seu estudo que 95% dos participantes realizaram o esquema de vacinação completo. Prado-Palos et al (2006); Moreira et al (2007); Garcia e Fachini (2008), constataram médias de até 13,5% de indivíduos que não completaram as três doses do esquema vacinal necessário para a obtenção da imunidade contra Hepatite B, observando ser um fato frequente a não realização do ciclo de vacinação. Milani et al (2011), citam que a vacina disponível no próprio emprego e sua gratuidade é fator contribuinte para melhor adesão.…”
Section: Resultsunclassified
“…Em estudo de soroprevalência da hepatite B desenvolvido em 2007, com profissionais de um Laboratório de Saúde Pública, não foi observada diferença estatisticamente significativa entre o sexo feminino e o sexo masculino, para os títulos de anti-HBs+ isolado. 21 A pesquisa identificou baixa cobertura vacinal entre os trabalhadores da instituição, com soroconversão de 28,8% para o anti-HBs e presença de não respondedores à vacinação. A taxa de soroconversão para o anti-HBs encontrada mostrou-se inferior à relatada em outros estudos, 22 (18,2%).…”
Section: Discussionunclassified